(untitled) (Clinics, 2012)
OBJECTIVE: To explore the use of β-lactoglobulin polymerized using microbial transglutaminase and heating to identify whether protein polymerization could reduce in vivo allergenicity and maintain in vitro and ex vivo immunoreactivity for use in tolerance-induction protocols. METHODS: Based on previous protocols applied in mice and children, we performed in vivo challenges (using a skin prick test) with native and polymerized β-lactoglobulin in adult patients with an IgE-mediated allergy to plactoglobulin. In vitro humoral immunoreactivity was analyzed using immunoblotting. Cell-mediated immunoreactivity was analyzed using ex vivo challenges with native and polymerized β-lactoglobulin and monitored by leukocyte adherence inhibition tests. RESULTS: The skin tests demonstrated that there was a significant reduction in immediate cutaneous reactivity after polymerization. Polymerization did not decrease the immunoblotting detection of s-IgE specific to β-lactoglobulin. Cell-mediated immunoreactivity, as assessed by ex vivo challenges and leukocyte adherence inhibition tests, did not exhibit significant differences between leukocytes challenged with native versus polymerized β-lactoglobulin. CONCLUSIONS: The polymerization of β-lactoglobulin decreased in vivo allergenicity and did not decrease in vitro humoral or ex vivo cell-mediated immunoreactivity. Therefore, we conclude that inducing polymerization using transglutaminase represents a promising technique to produce suitable molecules for the purpose of designing oral/ sublingual tolerance induction protocols for the treatment of allergies.